2016
DOI: 10.1158/0008-5472.can-15-3240
|View full text |Cite
|
Sign up to set email alerts
|

The PARP Inhibitor AZD2461 Provides Insights into the Role of PARP3 Inhibition for Both Synthetic Lethality and Tolerability with Chemotherapy in Preclinical Models

Abstract: The PARP inhibitor AZD2461 was developed as a next-generation agent following olaparib, the first PARP inhibitor approved for cancer therapy. In BRCA1-deficient mouse models, olaparib resistance predominantly involves overexpression of P-glycoprotein, so AZD2461 was developed as a poor substrate for drug transporters. Here we demonstrate the efficacy of this compound against olaparib-resistant tumors that overexpress P-glycoprotein. In addition, AZD2461 was better tolerated in combination with chemotherapy tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 49 publications
5
68
0
Order By: Relevance
“…Tumors from KB2P mouse donors were transplanted orthotopically into wild-type syngeneic mice, and when the tumor reached a volume >200 mm 3 , mice were treated with the PARPi AZD2461 for 28 consecutive days. Of note, PARPi AZD2461 is not a P-glycoprotein (Pgp) substrate, and therefore, acquired resistance to AZD2461 cannot be mediated by Pgp upregulation (Oplustil O’Connor et al, 2016). After an initial phase of response, the tumors eventually relapsed and were allowed to regrow to 100% volume, following which another treatment cycle was started.…”
Section: Resultsmentioning
confidence: 99%
“…Tumors from KB2P mouse donors were transplanted orthotopically into wild-type syngeneic mice, and when the tumor reached a volume >200 mm 3 , mice were treated with the PARPi AZD2461 for 28 consecutive days. Of note, PARPi AZD2461 is not a P-glycoprotein (Pgp) substrate, and therefore, acquired resistance to AZD2461 cannot be mediated by Pgp upregulation (Oplustil O’Connor et al, 2016). After an initial phase of response, the tumors eventually relapsed and were allowed to regrow to 100% volume, following which another treatment cycle was started.…”
Section: Resultsmentioning
confidence: 99%
“…2C,D). These events have also been known to mediate resistance in ovarian cancer patients (Swisher et al 2008;Patch et al 2015), showing the predictive potential of PDX models. The PDX models also revealed a novel resistance mechanism involving gene fusions that placed BRCA1 under transcriptional control of a heterologous promoter.…”
Section: Parpi Resistance Mechanisms In Brca-associated Breast Cancermentioning
confidence: 95%
“…Although the clinical relevance of P-gp up-regulation as cause of drug resistance remains controversial (AmiriKordestani et al 2012), expression of MDR1, the human counterpart of Abcb1, was recently found to be inversely correlated to olaparib response in human ovarian cancer cells (Vaidyanathan et al 2016). Such increased expression may result from complex genomic rearrangements that fuse a distant promoter to the MDR1 gene and thereby bypass the MDR1 promoter methylation (Patch et al 2015). The case of P-gp shows that a thorough mechanistic understanding is instrumental to combat resistant tumors-for example, by coadministration of tariquidar or by switching treatment to chemotherapeutics that are poor substrates for P-gp (Jaspers et al 2013).…”
Section: Parpi Resistance Mechanisms In Brca-associated Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These include BMN 673 (Biomarin) (24), niraparib (25), rucaparib (26), veliparib (27), and AZD2461 (28). In addition, the efficacy of some PARP inhibitors has been identified in non-BRCA-mutation-linked cancers, including sporadic castration-resistant prostate cancer and non-smallcell lung cancer.…”
mentioning
confidence: 99%